2013
DOI: 10.1017/s0950268813000435
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of norovirus gastroenteritis in Germany 2001–2009: eight seasons of routine surveillance

Abstract: SUMMARYWe analysed data on laboratory or epidemiologically confirmed cases (n = 856 539) and on outbreaks (n = 31 644) notified during week 31 (2001) to week 30 (2009), and performed molecular typing of specimens from 665 outbreaks. We aimed at identifying demographic and molecular characteristics to inform on potential additional approaches to prevent disease spread in the population. The mean incidence by norovirus season (week 31 in one year to week 30 in the following year) was 130 (range 19-300) cases/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 34 publications
5
49
2
4
Order By: Relevance
“…6 The viral study pathogens are not nationally notifiable in Australia, and so we applied population mortality rates for rotavirus and norovirus reported in two German studies to the 2010 Australian population. 35,36 For mild AGE cases (pathogen-specific), we subtracted the sum of outpatient, hospitalized, and fatal AGE cases from total AGE cases for each pathogen. This ensured internal consistency in our pathogen-specific estimates.…”
Section: Pathogen-specific Estimates Of Age Cases and Deathsmentioning
confidence: 99%
“…6 The viral study pathogens are not nationally notifiable in Australia, and so we applied population mortality rates for rotavirus and norovirus reported in two German studies to the 2010 Australian population. 35,36 For mild AGE cases (pathogen-specific), we subtracted the sum of outpatient, hospitalized, and fatal AGE cases from total AGE cases for each pathogen. This ensured internal consistency in our pathogen-specific estimates.…”
Section: Pathogen-specific Estimates Of Age Cases and Deathsmentioning
confidence: 99%
“…They are the causative agents of most nonbacterial infectious gastroenteritis worldwide (3)(4)(5). HuNoV infections spread rapidly, and outbreaks often take place in closed or semiclosed settings where communities gather (e.g., nursing homes, schools, hospitals, restaurants, and cruise ships) (6)(7)(8). Annually, HuNoVs cause an estimate of 21 million cases of acute gastroenteritis and 800 deaths in the United States alone (9, 10).…”
mentioning
confidence: 99%
“…4 Indeed, we found that 62 (87%) of the analysed outbreaks Interestingly, a single index case was identifiable in >75% of all outbreaks. This suggests that identification and the following management of this first case might be one of the most effective measures for prevention of norovirus outbreaks.…”
Section: Discussionmentioning
confidence: 66%
“…[1][2][3][4][5] Moreover, the clinical impact of norovirus infection in the vulnerable population of hospitalized, elderly, or immunosuppressed patients may even be more severe and prolonged than formerly suspected. [6][7][8][9][10] Even in otherwise healthy individuals norovirus infection may lead to post-infectious irritable bowel syndrome.…”
Section: Introductionmentioning
confidence: 99%